Barriers to innovation in Indian small and medium-sized enterprises - Anshul Pachouri; Sankalp Sharma (Asian Development Bank Institute (ADBI), 2016)
Innovation plays a critical role in shaping the industrial and firm competitiveness of any nation. Innovation is often discussed in the setting of developed countries, but the rise of emerging economies such as India has generated a new interest in understanding innovation in developing economies. This paper aims to study and present the current state of innovation in small and medium-sized enterprises (SMEs) in India. The focus of the paper is to bring out the key barriers SMEs face in the innovation process in the context of the existing government policy. India, being a developing nation, has its own set of unique situations and challenges that impede the innovation potential of SMEs operating in it. Many of these barriers are related to public policy, funding constraints, shortage of skilled research and development (R&D) workforce, and weak linkages between institutions and the firms, among others. The paper also discusses the existing government policy framework and enablers to support SMEs' innovation in India. It presents the key findings and recommendations in the form of policy suggestions to the government while taking into account the key challenges and enablers highlighted in the study.
Keywords: G20; G28; O38; 330; SME innovation; innovation policy framework; public policy barriers; innovation potential